2018
DOI: 10.3390/ma11010171
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behaviour and Galvanic Effects of Titanium Implants Coupled to Metallic Suprastructures in Artificial Saliva

Abstract: The aim of the present study is to analyze the electrochemical behavior of five different dental alloys: two cobalt-chromium alloys (CoCr and CoCr-c), one nickel-chromium-titanium alloy (NiCrTi), one gold-palladium alloy (Au), and one titanium alloy (Ti6Al4V), and the galvanic effect when they are coupled to titanium implants (TiG2). It was carried out by electrochemical techniques (open circuit measurements, potentiodynamic curves and Zero-Resistance Ammetry) in artificial saliva (AS), with and without fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
(53 reference statements)
2
34
0
Order By: Relevance
“…A large-area Pt electrode served as a counter electrode and a reference electrode, to which all potentials in the paper are referred, was an Ag|AgCl, 3.0 mol dm −3 KCl (E = 0.210 V vs. standard hydrogen electrode, SHE). Barrier properties of unmodified and modified Ti-implants were evaluated in solution based on Fusayama artificial saliva (0.4 g dm −3 NaCl, 0.4 g dm −3 KCl, 0.6 g dm −3 CaCl 2 ·2H 2 O, 0.58 g dm −3 Na 2 HPO 4 ·2H 2 O, and 1 g dm −3 urea), pH 6.8 [23], prepared from p.a. grade chemicals and redistilled water.…”
Section: Characterisation Methodsmentioning
confidence: 99%
“…A large-area Pt electrode served as a counter electrode and a reference electrode, to which all potentials in the paper are referred, was an Ag|AgCl, 3.0 mol dm −3 KCl (E = 0.210 V vs. standard hydrogen electrode, SHE). Barrier properties of unmodified and modified Ti-implants were evaluated in solution based on Fusayama artificial saliva (0.4 g dm −3 NaCl, 0.4 g dm −3 KCl, 0.6 g dm −3 CaCl 2 ·2H 2 O, 0.58 g dm −3 Na 2 HPO 4 ·2H 2 O, and 1 g dm −3 urea), pH 6.8 [23], prepared from p.a. grade chemicals and redistilled water.…”
Section: Characterisation Methodsmentioning
confidence: 99%
“…On the other hand, 316L stainless steel is susceptible to pitting corrosion when it is coupled to either Ti- or Co-based alloys [300]. Mellado-Valero et al [301] analysed the galvanic corrosion of CoCr, CoCr-c, NiCrTi, Au-Pd and Ti–6Al–4V dental alloys for implant superstructures when coupled to Ti grade 2 implants in artificial saliva (AS), with and without fluorides in different acidic conditions. It was concluded that NiCrTi is not recommended for implant superstructures due to the risk of Ni ion release to the body and that fluorides should be avoided in acidic media because Ti, Ti–6Al–4V and CoCr-c superstructures show galvanic corrosion.…”
Section: Mechanisms Of Corrosion In Vivomentioning
confidence: 99%
“…The method of electrochemical impedance spectroscopy (EIS) was applied to investigate the implant stability during exposure to a Fusayama artificial saliva solution (0.4 g dm −3 NaCl, 0.4 g dm −3 KCl, 0.6 g dm −3 CaCl 2 •2H 2 O, 0.58 g dm −3 Na 2 HPO 4 •2H 2 O, and 1 g dm −3 urea; pH 6.8 [46]) at the open circuit potential (E OCP ). The implant sample served as a working electrode (an area of 0.98 cm 2 ), an Ag|AgCl, 3.0 mol dm −3 KCl (E = 0.210 V vs. standard hydrogen electrode (SHE)) as a reference, and a platinum plate as a counter electrode.…”
Section: Characterization Of Implant Samplesmentioning
confidence: 99%